2019
DOI: 10.4236/ojog.2019.94045
|View full text |Cite
|
Sign up to set email alerts
|

Breast Milk: Its Role in Early Development of the Immune System and Long-Term Health

Abstract: Breast milk is the best source of nutrition that provides the energy and nutrients needed for the ideal growth and development of newborns and infants. Besides, breast milk includes various bioactive compounds, which protects infants against infectious agents and antigens and contributes to immune maturation, organ development and microbial colonization. Breast milk is dynamic; the composition of the nutrients and the content of immunological active compounds may change in each stage of lactation. During the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…Several studies have established that the host's susceptibility to infection is dependent on the age of the child and other protective maternal factors, such as transplacental antibodies (secretory IgG) and human milk (lysozyme, oligosaccharides, and lactoferrin). [ 21 22 ] As soon as breastfeeding is withdrawn (13–24 months), the child becomes highly susceptible to DEC infections. This susceptibility does not last for long.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have established that the host's susceptibility to infection is dependent on the age of the child and other protective maternal factors, such as transplacental antibodies (secretory IgG) and human milk (lysozyme, oligosaccharides, and lactoferrin). [ 21 22 ] As soon as breastfeeding is withdrawn (13–24 months), the child becomes highly susceptible to DEC infections. This susceptibility does not last for long.…”
Section: Discussionmentioning
confidence: 99%
“…Mothers caring for breastfeeding children with cancer's request for public support to care for their sick children may be due to the fact that, as breastfeeding mothers with sick children, they need to stay with their sick children at the hospital to nourish them frequently with enough breastmilk to boost the immunity of the child. Empirical studies have reported on the therapeutic effect of breastmilk on childhood cancer and child's immunity [51][52][53]. Mothers who understand the benefit of breastfeeding are unable to leave their breastfeeding sick children in an attempt to attend to their economic activities to raise some funds to support the care of their children.…”
Section: To Explore How Mothers Manage Under Such Circumstancesmentioning
confidence: 99%
“…Immunomodulatory activity in human milk is supported by reduction to allergies and immunerelated diseases in later life in the breastfed [63].…”
Section: Immune Modulationmentioning
confidence: 99%